The Impact of a Mediterranean Diet on the Gut Microbiome in Healthy Human Subjects: A Pilot Study - Rejeski, Jared J.; Wilson, Farra M.; Nagpal, Ravinder; Yadav, Hariom; Weinberg, Richard B. (Digestion, 2022)
Background and Aims: Despite the reported salutary benefits of a Mediterranean diet (MD) on a wide variety of health conditions, the specific microbial changes associated with an MD within the gastrointestinal (GI) tract are not well studied. Specifically, although population and survey-based studies have shown microbial changes, there are no published data on how an MD alters the gut flora in a controlled setting. Methods: We recruited 10 healthy subjects, each of whom gave a stool sample at baseline and then was provided with prepared meals of a “typical” American diet; after 2 weeks, a second stool sample was collected. All subjects were then provided with prepared meals based on the MD for another 2 weeks, followed by a final stool sample collection. Stool samples were batch analyzed with DNA extraction, and sequencing libraries were generated. Measures of bacterial diversity, species richness, and enterotypes were performed. Results: All ten subjects tolerated the diets well. Bacterial diversity increased with an MD, as measured by alpha diversity via the Simpson index. Furthermore, there were significant differences in 5 bacterial genera between the 2 diets. Conclusion: This small pilot study of controlled diets demonstrates that the MD can rapidly alter the gut microbiome in healthy subjects at the level of global microbial diversity and individual genera. These data confirm the findings of previous observational studies and establish the feasibility of conducting longer term studies on the impact of the MD on the flora of the GI tract and its relationship to digestive diseases.